Comparative Investigation on Small-Strain Stiffness Characteristics of Undisturbed and Compacted Highly Weathered Granites at Various Densities. (22nd October 2022) - Wang, Juntao; Kong, Lingwei; Yan, Junbiao; Zhou, Zhenhua
Abstract : To investigate the small-strain stiffness characteristics of highly weathered granite (HWG), a resonance column test system was used to conduct resonance column tests on highly weathered granite taken from the Lincang City, Yunnan Province, China. The effects of effective consolidation stress and structural changes is caused by remodeling process and initial dry density on the small-strain stiffness of HWG. Furthermore, the difference between the test data and other geotechnical materials were compared and analyzed. The test results show that the maximum dynamic shear modulus G max of remodeled highly weathered granite samples is greater than that of undisturbed samples once the effective consolidation stress is smaller than 300 kPa, but the opposite result is observed once the effective consolidation stress exceeds 300 kPa, and the phenomenon was also explained from a microscopic perspective based on the scanning electron microscopy (SEM). The G max of remodeled highly weathered granite gradually increases with the increase in dry density and effective consolidation stress. At an identical effective consolidation stress, the dynamic shear modulus ratio G / G max − γ curves of remodeled highly weathered granites at different initial dry densities are nearly consistent. Additionally, according to the test data, the mathematical model of G max for remodeled highly weathered granite considering effective consolidation pressure and initial dry density was established and agrees well with the test results of practical engineering cases. The range of variation in G / G max was given by the research results, which were compared with the G / G max of weathered granite obtained from the existing research, and the results in this work can provide a valuable reference for analyzing dynamic stability of buildings in the engineering construction of weathered granite sites.